STRATEGI GURU AKHLAK DALAM MENGHADAPI TANTANGAN PEMBELAJARAN DI KELAS 4 SD IT IHYA AS-SUNNAH SINGKUT. - WAHYU RIZKY RAMADHAN; Syaiful Anam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research stems from issues in shaping the character of fourth-grade students in the digital era at SD IT Ihya As-Sunnah Singkut. The purpose of this study is to identify the problems experienced by teachers and how to overcome them. Using a descriptive analytical qualitative approach, data were obtained through in-depth interviews, participatory observation, and document collection, and then analyzed using the interactive model developed by Miles, Huberman, and Saldana. The findings indicate that learning obstacles are largely caused by external factors: differences in family backgrounds, negative influences from peers, and disturbances caused by digital technology. Teachers use three integrated strategies to address these problems: (1) Collaborative Strategy by utilizing digital communication through WhatsApp groups to align the vision between school and home; (2) Managerial Strategy by conducting social engineering in the classroom, such as arranging seating and diverse study groups; and (3) Pedagogical Strategy by implementing the Joyful Learning method which includes Game-Based Learning, Storytelling, and interactive lectures. This method has been proven effective in increasing students' attention and reducing negative behavior.